Positive Discipline: Behavioral Management Skills for Parents and Teachers Part 2—General Approaches to Managing Behavior - Victor Harris; Whitney Fung; Sarah Ellis; Alison Schmeer (EDIS, 2015)
When a child is locked in the bathroom With water running And he says he is doing nothing But the dog is barking, Call 911. –Erma Bombeck